Fe3O4/HA nanocarriers of Curcumin to evaluate the anti-cancer effect in MCF-7 - Mehdi Sheikh Arabi; Seyedeh Zahra Hoseini (Golestan University Of Medical Sciences, 2023)
Background: Using magnetic nanoparticles has significant attention in various domains, including magnetic storage, medical therapies, and magnetic detection. Curcumin (diferuloylmethane), a polyphenol, is a low molecular weight active ingredient of the perennial herb Curcuma longa (commonly known as turmeric). Methods: The APTES-coated magnetite nanopowders were prepared as carriers for the anticancer drug "Curcumin" through the modified controlled chemical co-precipitation method. The concentration of Curcumin release in the HA-magnetite nanoparticles in 20 ml phosphate buffer (pH 7.4) within the PBS was determined at unique time intervals using UV-Vis Spectrophotometer as finished within the drug loading measurement. The in vitro cytotoxicity of the nanoparticles became assessed through MTT cellular viability assay after treating the MCF-7 breast adenocarcinoma cells with Curcumin-loaded APTES-covered magnetic NPs in addition to unloaded magnetic NPs in line with the manufacturer's commands. Results: The APTES and HA-coated and uncoated Fe3O4 nanoparticles were characterized by XRD, FE-SEM, FT-IR, Raman, and VSM techniques. The size of the Fe3O4 nanoparticles and their distribution were determined by Hydrodynamic length distribution. TEM results revealed that the average particle size is 15 nm. The VSM measurements showed that magnetic particles were superparamagnetic characteristics. Rapid Curcumin drug loading in 2 hrs and the controlled drug release in 1 hr ~15% and 48 hrs ~80% drug release was observed, applying to in-vitro applications. The obtained findings indicated that the APTES- Fe3O4/HA nanoparticles are promising for targeted Curcumin drug delivery applications. Conclusion: Curcumin-loaded MNPs were more potent than free Curcumin for inhibiting MCF-7 cell proliferation due to enhanced uptake in breast cancer cells. Due to high inherent magnetic properties, we may use the nanomedicine platforms for theranostic application after ensuring the MRI imaging abilities.